2021
DOI: 10.1063/5.0044824
|View full text |Cite
|
Sign up to set email alerts
|

A robust fiber-based quantum thermometer coupled with nitrogen-vacancy centers

Abstract: The nitrogen-vacancy center in diamond has been broadly applied in quantum sensing since it is sensitive to different physical quantities. Meanwhile, it is difficult to isolate disturbances from unwanted physical quantities in practical applications. Here, we present a fiber-based quantum thermometer by tracking the sharp-dip in the zero-field optically detected magnetic resonance spectrum in a high-density nitrogen-vacancy ensemble. Such a scheme can not only significantly isolate the magnetic field and micro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The NV center in diamond has been demonstrated to be a stable nanothermometer based on the ODMR thermal shift, , or the zero-phonon line (ZPL) ,, due to the thermally induced lattice strains. , It has been shown that the thermosensing capability of NV centers is hardly influenced by environmental factors, such as pH, ions, viscosity, and organic solvent, which renders them reliable thermometers even under complex biological environments. Besides, the excellent thermal conductivity of diamond ensures that all NV centers within a nanocrystal are in thermal equilibrium with the local environment.…”
Section: High-precision Bio-sensing At the Nanoscalementioning
confidence: 99%
See 2 more Smart Citations
“…The NV center in diamond has been demonstrated to be a stable nanothermometer based on the ODMR thermal shift, , or the zero-phonon line (ZPL) ,, due to the thermally induced lattice strains. , It has been shown that the thermosensing capability of NV centers is hardly influenced by environmental factors, such as pH, ions, viscosity, and organic solvent, which renders them reliable thermometers even under complex biological environments. Besides, the excellent thermal conductivity of diamond ensures that all NV centers within a nanocrystal are in thermal equilibrium with the local environment.…”
Section: High-precision Bio-sensing At the Nanoscalementioning
confidence: 99%
“…Many efforts, i.e. , the three-point method, frequency modulation scheme, , and coherent control methods , ( e.g. , Coop-D-Ramsey sequence), have also been developed to simplify and speed up the NV thermometry.…”
Section: High-precision Bio-sensing At the Nanoscalementioning
confidence: 99%
See 1 more Smart Citation
“…Nitrogen-vacancy (NV) color centers are emerging solid-state quantum sensors that can measure several physical quantities using different detection protocols due to the influence of physical quantities variations such as magnetic field [1,2] , electric field [3] , temperature [4][5][6][7] , and stress [8] . With the advantages of high spatial and temporal resolution, high sensitivity, stable signal, and quantum performance at room temperature, NV color centers can provide an effective means of characterization in a variety of fields, including biomedicine [9] , dark matter [10] , electrochemical signals [11] , etc.…”
Section: Introductionmentioning
confidence: 99%
“…While performance now rivals atomic-based sensors [44][45][46][47][48][49], solid-state systems still maintain much of the complexity of their atomic counterparts [49]. Whether measuring electromagnetic fields, temperature, or time [49][50][51][52][53][54][55][56][57], spin sensors perform three primary processes [44,49]: quantum state initialization, interaction with the environment, and readout. Initialization has seen little recent development and is nearly universally achieved optically [22].…”
Section: Introductionmentioning
confidence: 99%